Pro-Choice March Through Downtown San Francisco to City Hall - Watkins, Howard::::::::: (1989)
San Francisco 's "Queen's Bench Lawyers for PRO-CHOICE" on 5 foot stakes forming a wall in plaza; City Hall in background